Observation of inadvertent tube loss in ICU: effect of nasal bridles. (10th October 2019) - Allan, Kaylee; Taylor, Stephen; Clemente, Rowan; Toher, Deirdre
Abstract : Background: safe placement and securement of feeding tubes are essential to establishing early enteral nutrition. Nasogastric or nasojejunal feeding tubes are often inadvertently removed, and using a nasal bridle can reduce the number of tube replacements required. Aim: to review current nasal bridle practices on one intensive care unit. Over a 3-month period, nasal bridle use was recorded to measure unintentional tube loss and tube duration (the time a tube remained in situ). Method: an observational service evaluation. Findings: 109 patients were recruited; 205 tubes were passed and 77 bridles were inserted, with 42% ( n =46) of the bridles placed on day 1. Tubes secured with tape were more likely to be dislodged than tubes secured with a bridle, P=0.0001. Duration of tubes remaining in situ was significantly longer in patients who had a bridle fitted on day 1, P=0.0001 compared with tubes secured with tape. Conclusion: securing a tube with a nasal bridle from day 1 is independently associated with reduced tube loss, increased duration of tube use, and likelihood that the tube would reach redundancy when it was no longer required.